Evidence-Based Clinical Efficacy of Leukocyte and Platelet-Rich Fibrin in Maxillary Sinus Floor Lift, Graft and Surgical Augmentation Procedures - Damsaz, Mohamadamin; Castagnoli, Consuelo Zumarán; Eshghpour, Majid; Alamdari, Daryouosh Hamidi; Alamdari, Aida Hamidi; Noujeim, Ziad Eva Fouad; Haidar, Ziyad Samir (Frontiers in Surgery, 2020)
Leukocyte and Platelet-Rich Fibrin (L-PRF) is often associated with promising clinical results. Hence, this review aims to provide a 10-years update on the clinical effectiveness of L-PRF when applied/used as the “sole” biomaterial in maxillary sinus augmentation procedures. An electronic search using specific keywords for L-PRF and maxillary sinus augmentation was conducted in three main databases (PubMed-MEDLINE database, Google Scholar and Cochrane library) for the period between January 2009 – February 2020. The quest yielded a total of 468 articles. Based on the pre-established strict inclusion/exclusion criteria, only 7 articles were deemed eligible and included in the analysis. Surprisingly, of the 5 studies which used de-proteinized bovine bone mineral (DBBM) in combination with L-PRF, 60% acclaimed no significant effects and only 40% declared positive effects. Of the 2 articles which had used allogenous bone graft, 50% declared no significant effects and 50% acclaimed positive effects. Only 1 study had used L-PRF as the sole grafting material and reported a positive effect. Likewise, positive effects were reported in one other study using L-PRF in combination with a collagen membrane. Due to the heterogeneity of the included studies, this review is limited by the inability to perform a proper systematic meta-analysis. Overall, most of the published studies reported impressive results of L-PRF application as a grafting material (sole or adjuvant) in maxillary sinus augmentation and dental implant restorative procedures. Yet, distinct technical processing for L-PRF preparation was noted. Hence, studies should be approached with caution. Here in, in sinus lift and treatment of Schneider membrane, the formation of mature bone remains inconclusive. More studies are eagerly awaited in order to prove the beneficial or detrimental effects of PRFs, in general and L-PRFs, in specific; especially in their tissue regenerative potential pertaining to the promotion of angiogenesis, enhancing of cell proliferation, stimulation of cell migration and autocrine/paracrine secretion of growth factors, as well as to reach a consensus or a conclusive and distinct determination of the effect of leukocytes (and their inclusion) on inflammation or edema and pain; a call for regimenting the PRFs preparation protocols.